Development of natural frequency in multi-span composite bridges with variable cross-section: Analytical and numerical solutions. (November 2022) - Saglik, Huseyin; Balkaya, Can; Chen, Airong; Ma, Rujin; Doran, Bilge
Abstract: In this paper, the natural frequency of multi-span I-beam composite bridges with linear haunched cross-sections is studied analytically and numerically. Newton's eigenvalue iteration method is used in the analytical process to obtain the angular frequency by MATLAB. A variety of parameters affecting the natural frequency are investigated by validated finite element analysis (FEA). Based on the 143 FEA results, an easy-to-use formula is developed. The validity of the analytical method and the developed formula is demonstrated by numerical examples. It is shown that the developed formula can capture the natural frequency with high accuracy. The mean and maximum errors are found as 3.5% and 14%, respectively.